Exploring the relationship between the Mediterranean diet and weight loss maintenance: the MedWeight study - Poulimeneas, Dimitrios (2020)
© The Author(s), 2020. This is an Open Access article, distributed under the terms of the Creative Commons Attribution licence (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted re-use, distribution, and reproduction in any medium, provided the original work is properly cited.